HAEMATOLOGICAL ALTERATIONS IN HIV, MALARIA, AND CO-INFECTED PATIENTS ATTENDING THE HIV/AIDS CLINIC OF FEDERAL MEDICAL CENTER OWERRI IMO STATE, NIGERIA: A COMPARATIVE STUDY - Ejiofor, D. Chinedu; Edward, E. Bridget; Alisi, P. Ngozi; Raymond, A. Ude; Earnest, N. Emeka; Amah, C. Ifeanyi; Obi, A. Uchechukwu; Momodu, R. Iuebe; Samson, Abani; Ude, U. T. (FUDMA JOURNAL OF SCIENCES, 2025)
Blood parameters are typically altered in Human Immunodeficiency Virus (HIV) and malaria infections, and the extent of these alterations may vary due to several factors. These parameters can be used to determine the degree of damage resulting from the infections. The aim of this study was to assess changes in hematological parameters in individuals suffering from malaria, HIV, or co-infection of both diseases. With the aid of purposive sampling, a total of 165 adults attending the HIV/AIDS clinic at the Abia State University Teaching Hospital were recruited for the study after providing consent. They were categorized into Group I (30 HIV-positive individuals), Group II (53 malaria-positive individuals), Group III (52 individuals co-infected with malaria and HIV), and Group IV (30 individuals with neither HIV nor malaria). HIV and malaria parasite infections were screened using standard procedures. Hematological indices were examined using standard procedures. The PCV, Hb, WBC, platelets, and neutrophils were reportedly highest in HIV patients but lowest in co-infected patients. However, a contrary observation was made on the lymphocytes. The hematological indices reported for the control group were significantly (p<0.05) higher than those reported for each of the groups I-III. Thus, it can be deduced from this study that malaria and HIV co-infection have deleterious health consequences on sufferers. Therefore, government policies aimed at ameliorating the severity and hardships experienced by HIV patients should ensure that the chances of co-infection are significantly reduced.